THE EFFECT OF CONSUMPTION OF LONG BEAN LEAVES (VIGNA SINENSIS) ON INCREASING ASI PRODUCTION IN BREASTFEEDING MOTHERS IN THE WORKING AREA OF PUSKESMAS PEBAYURAN DISTRICT BEKASI - Suryani, Wiwin; Assyaidah, Sonda Nur (HEARTY, 2025)
Babies really need breast milk, especially at the beginning of life. Breast milk is good food for babies because it contains lots of nutrients and can provide natural immunity. Many mothers stop giving exclusive breastfeeding because they feel that their breast milk is not sufficient for the baby's needs. The problem of the process of releasing breast milk not flowing smoothly is one of the reasons why someone cannot breastfeed their baby so that the breastfeeding process is disrupted. The aim of this research is to determine the effect of consuming long bean leaves on increasing breast milk production in breastfeeding mothers in the Pebayuran Community Health Center Work Area, Bekasi Regency in 2023.This research uses the Pre Experiment Statistics Comparison Group research type. The population in this study was 34 breastfeeding mothers. The sampling technique used in this research was a total sampling technique of 34 people. Results data analysis used univariate and bivariate analysis (Mann-Whitney). The research results showed that the mean weight rank of babies in the control group who were not given long bean leaves was 20.31, while the weight of babies in the intervention group after being given long bean leaves was 48.69. The results of the statistical test show a value of p = 0.000, which is greater than the significance level, namely α = 0.05, so it can be concluded that Ho is rejected and Ha is accepted. The conclusion of this research is that there is an effect of consuming long bean leaves on increasing breast milk production in breastfeeding mothers in the Pebayuran Community Health Center working area, Bekasi Regency. Suggestions for respondents to continue consuming long bean leaves to increase breast milk production in all breastfeeding mothers in the hope of maintaining or increasing mothers' breast milk production.